Comparative Effectiveness of Coriander Seed Decoction and Unripe Coconut Water in Lowering Uric Acid Level - Anggraini, Thalitha Ayu; Manafe, Derri R. Tallo; Nurina, Rr. Listyawati; Ratu, Kristian (Universitas Nusa Cendana, 2024)
Background: High uric acid levels are a major cause of Gout arthritis. Untreated Gout arthritis can progress to chronic gout, kidney dysfunction, and a decrease in quality of life. The use of natural substances such as the giving of coriander seed decoction and unripened coconut water can be one of the non-pharmacological intervention to reduce uric acid levels. Objective: This research aims to determine the comparison of the effectiveness of coriander seed decoction and unripened coconut water in reducing uric acid levels. Methods: The study is a quasi-experimental research, using a pretest-posttest with control group design. The study participants consisted of 54 respondents from educators and education staff at Nusa Cendana University who met the inclusion and exclusion criteria. Data analysis used parametric analysis, namely paired sample t-test, and one-way anova. Result: There was a significant effect in the coriander seed decoction intervention group on uric acid levels before and after the intervention (p=0.002), while in the unripened coconut water intervention group and the control group, there was no significant effect on uric acid levels with respective p-values of (p=0.648) and (p=0.705). There was no significant difference after the intervention in the coriander seed decoction group, unripened coconut water group, and control group in reducing uric acid levels (p=0.114). Conclusion: There was no difference in the effectiveness between giving coriander seed decoction and unripened coconut water to reduce uric acid levels.